Effect of UGT2B7 -900G>A (-842G>A; rs7438135) on morphine glucuronidation in preterm newborns: results from a pilot cohort. (September 2014) - Matic, Maja; Norman, Elisabeth; Rane, Anders; Beck, Olof; Andersson, Maria; Elens, Laure; Tibboel, Dick; Fellman, Vineta; van Schaik, Ron HN
Aim: Assess association between UGT2B7 polymorphism -900G>A (rs7438135, also known as -842G>A) with morphine kinetics in preterm newborns undergoing mechanical ventilation.Materials & methods: Thirty-four infants were enrolled in a randomized clinical trial and allocated to rapid sequence intubation with remifentanil (1 µg/kg) or morphine (0.3 mg/kg). The latter group was included in our study.Results: Morphine plasma concentrations at 20 min post intubation were associated with postnatal age (p = 0.017) and UGT2B7 -900G>A (p = 0.036). UGT2B7 -900A allele carriers (n = 13) had lower morphine levels compared with UGT2B7 -900G/G patients (n = 2). Morphine-3-glucuronide and morphine-6-glucuronide plasma concentrations were only found to be associated with gestational and postnatal age. However, -900A allele carriers had a higher morphine-3-glucuronide:morphine metabolic ratio compared with patients genotyped as -900G/G (p = 0.005), as determined by linear regression.Conclusion : Our small pilot study illustrates that in addition to gestational and postnatal age, the UGT2B7 -900G>A polymorphism significantly alters morphine pharmacokinetics in preterm infants. Original submitted 8 April 2014; Revision submitted 22 July 2014